2017
DOI: 10.3390/cli5040085
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Networks in Agricultural Adaptation to Climate Change: Implications for Sustainable Agriculture in Pakistan

Abstract: Abstract:Incorporating adaptation into subsistence farming systems is an important strategy to reduce damages related to climate change and to protect livelihoods in developing countries. Using a dataset of 450 farm households collected from three agro-ecological zones, this study examines rural networks, assesses farm-level institutional support and documents any existing structural gaps on climate change adaptation in the agricultural sector of Pakistan. For this purpose, a social network analysis method is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Cities deliver emergency services for evacuation and relief in case of occurrence of a flood event and provide avenues to diversify their income [36,38]. Moreover, cities provide various services like health, credits, agriculture extension, livelihood, and farm management training that help rural households during and after a flood event [101,102]. In the aftermath of a flood, a city provides durable and non-durable goods through markets and aid agencies, for example, material for shelter and house construction, fertilizers, tools and technology, and food items that help rural households to cope and revive their livelihoods [103,104].…”
Section: Goods and Servicesmentioning
confidence: 99%
“…Cities deliver emergency services for evacuation and relief in case of occurrence of a flood event and provide avenues to diversify their income [36,38]. Moreover, cities provide various services like health, credits, agriculture extension, livelihood, and farm management training that help rural households during and after a flood event [101,102]. In the aftermath of a flood, a city provides durable and non-durable goods through markets and aid agencies, for example, material for shelter and house construction, fertilizers, tools and technology, and food items that help rural households to cope and revive their livelihoods [103,104].…”
Section: Goods and Servicesmentioning
confidence: 99%
“…Indeed, adoption of a technological innovation in West Africa depends on a good understanding of technology but also on belonging to a strong social network (Diagne, Glover, Groom, & Phillips, 2012b). Social networks play a key role in improving the adaptive capacity of farming communities to climate change (Abid, Ngaruiya, Scheffran, & Zulfiqar, 2017;Vaughan & Dessai, 2014). Women can also be an effective dissemination channel because they may have greater tendency to share information beyond the household as mentioned by a farmer during the focus group discussion.…”
Section: Needs Of Cis and Dissemination Channelsmentioning
confidence: 99%
“…In Pakistan a number of researchers (for instance, Hanif et al, 2010;Rasul et al, 2012;Zhu et al, 2013) have examined the effects of climate change on agriculture. Additionally, several previous studies on adaptation of agriculture to climate change in Pakistan (for example, Ali and Erenstein, 2017;Abid et al, 2018Abid et al, & 2017Arshad et al, 2016Arshad et al, , 2017Gorst et al, 2015). The available literature has reported that there limited adaptation of climate change at farm level and emphasized the need for more research to examine the factors affecting local understanding of climate change and adaptation behavior.…”
Section: Introductionmentioning
confidence: 99%